Causes and Consequences of Transfer Pricing Conflict: Evidence from the Service Sector - Bülend Terzioğlu; Adam Steen (Journal of Accounting, Business and Management (JABM), 2014)
Conflicts emanating from transfer pricing have far-reaching consequences for interdivisional cooperation, sharing of information, goal congruence, employee motivation and performance. Few researchers have explicitly focused on the nature of transfer pricing conflict in organizations, particularly with respect to service organizations. The aim of this paper is to examine the nature of transfer pricing conflicts and the manner in which these conflicts are resolved within the Australian service sector. We conducted an exploratory survey supported by interviews with selected senior management. Our results reveal that the majority of organizations experience frequent conflicts arising from transfer pricing and that most of these conflicts are resolved through direct negotiation between the disputing parties. The paper concludes with suggestions of avenues for further research.